1965
DOI: 10.1172/jci105268
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in pulmonary diffusing capacity and pulmonary capillary blood volume with negative pressure breathing.

Abstract: In 1915 Krogh first reported that the breathholding pulmonary diffusing capacity for carbon monoxide (DL) is increased during exercise (1). Although change in the volume of blood in the pulmonary capillary bed (Vc), as determined by change in DL, can be produced by several mechanisms, it is during exercise that the greatest changes are observed. Yet, in a previous investigation in which some of the physiologic changes of exercise were simulated, such as alterations in alveolar ventilation, alveolar volume, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…There was no decrease in D m compared with the measurement made after 30 s of CNP suggesting that there was no induction of an interstitial oedema. Steiner et al (1965) observed an increase in V c and D m after applying high CNP for either 4 or 7 min (−26 to −52 cmH 2 O) in five subjects.…”
Section: Discussionmentioning
confidence: 82%
“…There was no decrease in D m compared with the measurement made after 30 s of CNP suggesting that there was no induction of an interstitial oedema. Steiner et al (1965) observed an increase in V c and D m after applying high CNP for either 4 or 7 min (−26 to −52 cmH 2 O) in five subjects.…”
Section: Discussionmentioning
confidence: 82%
“…First, negative intrathoracic pressure can collapse the great veins and limit venous return [7]. Additionally, negative intrathoracic pressure may increase the risk of pulmonary edema or atelectasis [1214]. Finally, it is unclear how the variety of different negative pressure techniques differs from one another.…”
Section: Introductionmentioning
confidence: 99%
“…Both immersion in water (124) and negative pressure breathing (125) increase DLco as a consequence of the increase thereby caused in pul monary capillary blood volume. In forward acceleration.…”
Section: Transfer Of Gases Inmentioning
confidence: 99%